Intercultural Interaction between VietNamese Military Students and Foreign Teachers in English Classroom Context: A Case Study of a Military School - Ngô, Thị Chúc (ĐHNN, 2017)
This study explores the intercultural interaction between Vietnamese military students and foreign teachers in English classroom context as well as the participants’ perceptions of those interactions using qualitat ive case study methodology. The participants are a class of 18 Vietnamese military students and two foreign teachers in a military school in Hanoi. Four data collection instruments were employed: classroom observation, retrospective interviews, focus group interviews and individual open - ended interviews. The interaction were analyzed using Chaudron’s (1988) interactive features of classr oom behaviours and Hofstede’s (1986) nature of teacher - student interaction related to individualism versus collectivism and power distance dimensions of culture. The findings show that the teacher - student intercultural interaction had the characteristics of both individualism and collectivism, and both large power distance and small power distance. The students participated quite actively in the lessons. The foreign teachers align themselves with their own teaching styles with lots of communicative activities during the lessons and independence of students was encouraged. However, there was a mismatch between the students’ and teachers’ expectations. The perceptions of both students and teachers about their classroom interaction were positive. Both student and teacher participants in this study perceive that differences between two cultures do not hinder their intercultural interaction in the classroom. Nevertheless, misunderstanding was hidden during the interaction without being conscious of by both students and teachers. The findings raise awareness of cultural differences for both students and teachers involved in intercultural interaction in the classroom. The study proposes practical suggestions for international teachers of English in Vietnam and Vietna mese students who study English with foreign teachers in their home country or go overseas to study, especially in Australia